Pengetahuan dan Perilaku Pencarian Pelayanan Kesehatan Reproduksi Pada Remaja di Kota Bengkulu - Rafidaini Sazarni Ratiyun; Loren Juksen (Universitas Pahlawan Tuanku Tambusai, 2023)
The utilization of reproductive health services by adolescents is still low Objective: to determine the relationship between knowledge and behavior of adolescent sexual and reproductive health services in high school students in Bengkulu City. Methods: The design of this study was cross-sectional. The population in this study were all high school students in Bengkulu City with a sampling technique using proportional random sampling, with a total sample of 395 respondents. Collecting data using a questionnaire, univariate and bivariate analysis using the Chi-Square test. Results: 44.1% of adolescents have good knowledge about sexual and reproductive health. There are 20% of adolescents who have sought sexual and reproductive health services in adolescents. There was no relationship between knowledge and behavior of adolescent sexual and reproductive health services (p<0.005). Conclusion: The results show that knowledge about adolescent reproductive health is still low, and the search behavior for adolescent reproductive health services is still low.